Everything, every day, all at once—why we need to ask less of medical students. (30th November 2022) - Politis, Marina; Hodkinson, Joy
Abstract : To improve the wellbeing of medical students and future doctors we need to challenge our culture of relentless productivity, say Marina Politis and Joy Hodkinson